2021
DOI: 10.21203/rs.3.rs-830142/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent evolution of a nutritional symbiosis in ants

Abstract: Ants are among the most successful organisms on earth. It has been suggested that forming symbioses with nutrient-supplementing microbes may have contributed to their success, by allowing ants to invade otherwise inaccessible niches. However, it is unclear whether ants have repeatedly evolved symbioses to overcome the same nutrient limitations. Here, we address this question by comparing the independently evolved symbioses in Camponotus, Cardiocondyla, Formica and Plagiolepis ants. Our analysis reveals the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…As previously reported by Jackson et al (2022), we found that Liliensternia is restricted to a single clade of Serviformica ants, while Wolbachia is present in every species screened and the majority of queens screened overall (112/131). Wolbachia is not only widely distributed among Formica species but also highly abundant, accounting for 54% of all sequences across all queens analysed.…”
Section: Four Common Bacterial Genera Are Associated With Formica Antssupporting
confidence: 87%
See 3 more Smart Citations
“…As previously reported by Jackson et al (2022), we found that Liliensternia is restricted to a single clade of Serviformica ants, while Wolbachia is present in every species screened and the majority of queens screened overall (112/131). Wolbachia is not only widely distributed among Formica species but also highly abundant, accounting for 54% of all sequences across all queens analysed.…”
Section: Four Common Bacterial Genera Are Associated With Formica Antssupporting
confidence: 87%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted January 21, 2023. ; https://doi.org/10.1101/2023.01.20.524858 doi: bioRxiv preprint mirrored in all phylobiome trees. We expected this pattern in the full phylobiome tree, because one clade of Serviformica carries Liliensternia, a strictly vertically transmitted symbiont whose phylogeny mirrors that of its host (Jackson et al, 2022). However, even when we considered trees of the single bacterial genera Spiroplasma, Wolbachia, and Lactobacillus, the paraphyletic pattern was still apparent (Fig.…”
Section: Phylosymbiosis In Formica Antsmentioning
confidence: 95%
See 2 more Smart Citations
“…In lineages that contain endosymbionts, these cells become bacteriocytes whereas in other lineages they contribute to the midgut. Consistently, it has been shown that in the ant lineage within the genera Formica and Cardiocondyla, and in some lineages of beetles of subfamily Cassidinae, endosymbiosis has been repeatedly lost but the relics of the existence of bacteriocytes or bacteriocyte-like cells have been retained (Lilienstern, 1932;Jackson et al, 2021;Fukumori et al, 2022). Moreover, when endosymbionts are experimentally removed from A. pisum aphids and C. floridanus ants the bacteriocytes are still specified and migrate to the midgut epithelium (Braendle et al, 2003;Stoll et al, 2010;Rafiqi et al, 2020).…”
Section: Discussionmentioning
confidence: 90%